A feasible way to remove the heat during adsorptive methane storage - Gütlein, Stefan; Burkard, Christoph; Zeilinger, Johannes; Niedermaier, Matthias; Klumpp, Michael; Kolb, Veronika; Jess, Andreas; Etzold, Bastian (Environmental Science & Technology, 2015)
Methane originating from biogas or natural gas is an attractive and environmentally friendly alternative to gasoline. Adsorption is seen as promising storage technology, but the heat released limits fast filling of these systems. Here a lab scale adsorptive methane storage tank, capable to study the temperature increase during fast filling, was realized. A variation of the filling time from 1 h to 31 s, showed a decrease of the storage capacity of 14% and temperature increase of 39.6 °C. The experimental data could be described in good accordance with a finite element simulation solving the transient mass, energy, and impulse balance. The simulation was further used to extrapolate temperature development in real sized car tanks and for different heat pipe scenarios, resulting in temperature rises of approximately 110 °C. It could be clearly shown, that with heat conductivity as solei mechanism the heat cannot be removed in acceptable time. By adding an outlet to the tank a feed flow cooling with methane as heat carrier was realized. This setup was proofed in simulation and lab scale experiments to be a promising technique for fast adsorbent cooling and can be crucial to leverage the full potential of adsorptive methane gas storage.
CRIS-Team Scopus Importer:2023-08-15